Physical dependence in older adults and job burnout in their informal caregivers in the COVID-19 context, a correlational study - Reyes-Jarquín, Karina; Ortiz-Rojas, Beatriz (Universidad y Salud, 2023)
Introduction: The functional status of older adults (OA) is usually used as an indicator of their health. Increased dependence raises the need for an informal caregiver (IC), leading to a state of work overload, which was frequently observed during the COVID-19 confinement. Objective: To assess the relationship between physical dependence of OA, job burnout of their IC, and the confinement conditions in the context of the COVID-19 pandemic. Materials and methods: The participants included 77 OA together with their respective IC. The OA filled out a sociodemographic data sheet and a Confinement Conditions Questionnaire. In addition to these two forms, the IC filled out the Zarit Caregiver Burnout Scale and the ABVD Barthel Scale. Results: Statistically significant correlations were found between: physical dependence and job burnout (rho=0.475, p<0.01); physical dependence and confinement degree (rho=0.441, p<0.01); and job burden and confinement degree (rho=0.344, p<0.01). Conclusion: Caregivers develop a greater job burnout as a consequence of the OA’s dependence. Furthermore, it seems that this burnout is more related to the confinement conditions experienced by older adults than to the caregiver’s own conditions.